Differences of the primary energy consumption of the countries all over the world - Tóth, Judit; Magda, Róbert (Applied Studies in Agribusiness and Commerce, 2017)
The global energy consumption is continuously growing, because the population of Earth and the standard of living expands day by day. As a result, the emission of greenhouse gases increases further more. The various countries use the different types of fuels in varying amount.In this study we have examined the primary energy consumption of the countries, according to the BP Statistical Review of World Energy June 2016 (BP, 2016), based upon their usage of fuels.The assay resulted in a 7 cluster model. With one exception, each cluster contains a resource, which is used in a much larger amount than in the other clusters. As a result, we may differentiate between an average cluster, and the clusters of countries that use primarily hydropower, nuclear energy, renewable energy, coal, fossil oil, and natural gas.We have examined if there is any connection between the location of a country in a cluster and its HDI, as well as the countries’ competitiveness.JEL Code: Q42, Q43, Q35, Q01, P28, P18